Narrative of an Attempt to Reach the North Pole In Boats Fitted for the Purpose, and Attached to His Majesty's Ship Hecla, in the Year MDCCCXXVII, under the Command of Captain William Edward Parry - Parry, William Edward 1790-1855 (Cambridge University Press, 1828)
One of the leading Arctic navigators of his age, William Edward Parry (1790–1855) led three expeditions in search of the North-West Passage (accounts of which are also reissued in this series). Parry's early career had been spent protecting the whaling fleet of Spitsbergen and this experience led him in 1826 to propose to the Admiralty an expedition to the North Pole. In order to reach further north than earlier attempts, Parry used sledge-boats that could be towed over the ice on runners, and then take to any open sea that the crew encountered. In 1827 the expedition attained a record latitude that stood for nearly fifty years. This illustrated account, published in 1828, was described by the Quarterly Review as a record of 'the patient, persevering, energetic, and undaunted conduct which British seamen are capable of displaying, in the most difficult, discouraging, and dangerous circumstances'
Keywords: Hecla (Ship); North Pole; Arctic regions / Discovery and exploration / British